Pengaruh Kecukupan Modal, Likuiditas, dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2020–2024 - Arshella Amanda Putrie Prastarie; Indra Lila Kusuma; Sri Laksmi Pardanawati (Lembaga Yasin AlSys, 2026)
This study was motivated by fluctuations in the value of banking companies amid post-pandemic economic recovery and global uncertainty, making it important to examine the factors that influence firm value in the banking sector. This study aims to analyze the influence of capital adequacy, liquidity, and profitability on firm value in banking companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study employed a quantitative approach with a causal design. The research sample consisted of 19 banking companies selected using purposive sampling, with a total of 95 observational data. Data were obtained from annual financial reports and analyzed using multiple linear regression with the assistance of SPSS. Capital adequacy was measured using the Capital Adequacy Ratio (CAR), liquidity using the Loan to Deposit Ratio (LDR), profitability using Return on Assets (ROA), and firm value using Price to Book Value (PBV). The results showed that capital adequacy, liquidity, and profitability simultaneously had a significant influence on firm value. Partially, capital adequacy had no significant influence on firm value, liquidity had a significant negative influence, whereas profitability had a significant positive influence on firm value. The conclusion of this study affirms that profitability is the most influential factor in increasing the value of banking companies, while liquidity management is an important consideration for investors. The implications of this study indicate that banking companies need to improve profitability, optimize asset management, and maintain liquidity stability to strengthen firm value.